THE USE OF ALUMINUM AND ITS ALLOYS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Aluminum alloys - alloys consisting mainly of aluminum. Aluminum alloys are prepared by adding Si, Mg, Zn, Mn, Ni, Fe, Ti and other elements to aluminum separately or in certain combination and liquefying it [1,2].